2010
DOI: 10.1099/vir.0.021212-0
|View full text |Cite
|
Sign up to set email alerts
|

Size and mechanical stability of norovirus capsids depend on pH: a nanoindentation study

Abstract: Norovirus-like particles were imaged using atomic force microscopy. The mechanical stability of the virus-like particles (VLPs) was probed by nanoindentation at pH values ranging from 2 to 10. This range includes pH values of the natural environment during the life cycle of noroviruses. The resistance of VLPs to indentation was constant at acidic and neutral pH. The Young's modulus was of the order of 30 MPa. At basic pH the compliance of the capsid increased along with an increase in diameter. This specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 41 publications
6
41
0
Order By: Relevance
“…Developments in atomic force microscopy (AFM) (7,8) have recently led to the experimental investigation of the mechanical properties of single virus particles (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The mechanical elasticity of virions and capsids can be probed using the approach pioneered in ref.…”
mentioning
confidence: 99%
“…Developments in atomic force microscopy (AFM) (7,8) have recently led to the experimental investigation of the mechanical properties of single virus particles (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The mechanical elasticity of virions and capsids can be probed using the approach pioneered in ref.…”
mentioning
confidence: 99%
“…The capsids observed irreversible deformation for indentation forces close to 1 nN. Our own work on Norovirus (NV) virus-like particles showed a relationship between stiffness and size on one hand and the pH value on the other hand (Cuellar, et al, 2010). It was concluded that these changes are related to a modulation of non-covalent interactions among the capsomers by the pH.…”
mentioning
confidence: 93%
“…The exceptional mechanical stability found for the HSV-1 virus might be a key factor for the survival during transport over long distances of the axonal cytoplasm where is exposed to mechanical stresses by molecular motors before it reaches its final point for cargo release (Liashkovich, et al, 2008). The reported mechanical stability and self-healing mechanism in Norovirus capsids (Cuellar, et al, 2010) with regard to drastic changes in pH may be an essential requirement for infection. To succeed as a pathogen the capsid has to survive the highly acidic pH in the stomach and become infectious under the weakly basic conditions within the ileum.…”
Section: Viral Mechanics and The Infection Cyclementioning
confidence: 99%
See 2 more Smart Citations